Safety and efficacy of natalizumab in patients with acute ischaemic stroke (ACTION): a randomised, placebo-controlled, double-blind phase 2 trial. Issue 3 (March 2017) - Elkins, Jacob; Veltkamp, Roland; Montaner, Joan; Johnston, S Claiborne; Singhal, Aneesh B; Becker, Kyra; Lansberg, Maarten G; Tang, Weihua; Chang, Ih; Muralidharan, Kumar; Gheuens, Sarah; Mehta, Lahar; et al.
Summary: Background: In animal models of acute ischaemic stroke, blocking of the leukocyte-endothelium adhesion by antagonism of α4 integrin reduces infarct volumes and improves outcomes. We assessed the effect of one dose of natalizumab, an antibody against the leukocyte adhesion molecule α4 integrin, in patients with acute ischaemic stroke. Methods: In this double-blind, phase 2 study, patients with acute ischaemic stroke (aged 18–85 years) from 30 US and European clinical sites were randomly assigned (1:1) to 300 mg intravenous natalizumab or placebo with stratification by treatment window and baseline infarct size. Patients, investigators, and study staff were masked to treatment assignments. The primary endpoint was the change in infarct volume from baseline to day 5 and was assessed in the modified intention-to-treat population. Secondary endpoints were the change in infarct volume from baseline to day 30, and from 24 h to days 5 and 30; the National Institute of Health Stroke Scale (NIHSS) at baseline, 24 h, and at days 5 (or discharge), 30, and 90; and modified Rankin Scale (mRS) and Barthel Index (BI) at days 5 (or discharge), 30, and 90. This trial is registered withClinicalTrials.gov, numberNCT01955707 . Findings: Between Dec 16, 2013, and April 9, 2015, 161 patients were randomly assigned to natalizumab (n=79) or placebo (n=82). Natalizumab did not reduce infarct volume growth from baseline to day 5 compared with placebo (median absolute growth 28 mL [range −8 to 303] vs 22 mL [−11 to 328]; relative growth ratio 1·09 [90% CI 0·91–1·30], p=0·78) or to day 30 (4 mL [−43 to 121] vs 4 mL [−28 to 180]; 1·05 [0·88–1·27], p=0·68), from 24 h to day 5 (8 mL [−30 to 177] vs 7 mL [−13 to 204]; 1·00 [0·89–1·12], p=0·49), and from 24 h to day 30 (−5 mL [−93 to 81] vs −5 mL [−48 to 48]; 0·98 [0·87–1·11], p=0·40). No difference was noted between the natalizumab and placebo groups in the NIHSS (score ≤1 or ≥8 point improvement) from baseline at 24 h, day 5 (or discharge), day 30 (27 [35%] vs 36 [44%]; odds ratio 0·69 [90% CI 0·39–1·21], p=0·86), and day 90 (36 [47%] vs 37 [46%]; 1·10 [0·63–1·93], p=0·39). More patients in the natalizumab group than in the placebo group had mRS scores of 0 or 1 at day 30 (13 [18%] vs seven [9%]; odds ratio 2·88 [90% CI 1·20–6·93], p=0·024) and day 90 (18 [25%] vs 16 [21%]; 1·48 [0·74–2·98], p=0·18); and BI (score ≥95) at day 90 (34 [44%] vs 26 [33%]; 1·91 [1·07–3·41], p=0·033) but not significantly at day 5 or day 30 (26 [34%] vs 26 [32%]; 1·13 [0·63–2·00], p=0·37). Natalizumab and placebo groups had similar incidences of adverse events (77 [99%] of 78 patients vs 81 [99%] of 82 patients), serious adverse events (36 [46%] vs 38 [46%]), and deaths (14 [18%] vs 13 [16%]). Two patients in the natalizumab group died because of adverse events assessed as related to treatment by the investigator (pneumonia, and septic shock and multiorgan failure). Interpretation: Natalizumab administered up to 9 h after stroke onset did not reduce infarct growth. Treatment-associated benefits on functional outcomes might warrant further investigation. Funding: Biogen.